2003
DOI: 10.1046/j.1525-1497.2003.20826.x
|View full text |Cite
|
Sign up to set email alerts
|

“They treated me like a leper”

Abstract: OBJECTIVE: Hepatitis C virus is the most prevalent chronic blood-borne infection in the United States, typically acquired through contaminated blood products or needle sharing. We hypothesized that patients with chronic hepatitis C infection experience stigmatization independent of mode of acquisition and that it negatively affects quality of life. DESIGN:Cross-sectional observation study. SETTING:Specialty clinic in a tertiary referral hospital. PATIENTS:Two hundred and ninety outpatients diagnosed with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(66 citation statements)
references
References 36 publications
3
60
0
3
Order By: Relevance
“…[10111213] Research findings have revealed that people living with infectious diseases frequently are marginalized and experience considerable stigmatization. [101112] Hepatitis carriers have been described as modern-day “lepers”[14] or “AIDS,”[15] and individuals with HBV as well as their families have felt ashamed about having HBV. [14]…”
Section: Introductionmentioning
confidence: 99%
“…[10111213] Research findings have revealed that people living with infectious diseases frequently are marginalized and experience considerable stigmatization. [101112] Hepatitis carriers have been described as modern-day “lepers”[14] or “AIDS,”[15] and individuals with HBV as well as their families have felt ashamed about having HBV. [14]…”
Section: Introductionmentioning
confidence: 99%
“…Social factors, including stigma related to HCV and substance use, act as system- and provider-level barriers to HCV treatment (Butt, 2008; Harris and Rhodes, 2013; Lekas et al, 2011; Sgorbini et al, 2009; Swan et al, 2010; Treloar et al, 2013; Zickmund et al, 2003, 2012). Health-care settings, in particular, are frequently associated with HCV-related stigma and discrimination by current and former substance users (Harris and Rhodes, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…HCV- and substance use-related stigma have been associated with reluctance to disclose HCV status, initiate HCV treatment, and engage in HCV care (Astone-Twerell et al, 2006; Evon et al, 2013; Paterson et al, 2007; Zickmund et al, 2003). While the side effect profiles of interferon-based treatment for HCV likely prevented some HCV-infected individuals from initiating HCV treatment, the advent of lower side effect burden HCV treatment options has reduced individual-level barriers related to side effects (Wei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C is a stigmatized disease associated to illegal drugs use, HIV/AIDS and promiscuity (ZICKMUND et al, 2003). However, the results found show that most patients of HCV infected group had a stable relationship with a regular partner and only one sexual partner.…”
Section: Discussionmentioning
confidence: 84%